Spatial Modelling of Religious Tourism Development Strategy with Special Reference of Aer Mata Cemetery Bangkalan Madura, Indonesia - Katherine E.D.P Permanasari; Endang Titi Sunarti Darjosanjoto; Murni Rachmawati (IPTEK Journal of Proceedings Series, 2015)
The development of tourism in Indonesia can be classified based on the type of tourism attraction preferred. Bangkalan Regency determine religious tourism as a major tourism destination. This is as affected by the existence of a number of historical relics which are related to the spread of Islam on Madura Island. , It also asserts this Cemetery as urban heritage that must be protected in Bangkalan. This study explores  Cemetery Aer Mata, this religious tourism destination layout has not been arranged properly. For this reason, formulation of the zone mapping  in the area is needed, in order to be developed as tourism destination that contains a historical value and consistent with regional policy for conservation. An spatial modeling can be develop as tourism strategy by using cognitive mapping techniques.